A short course in soil and rock slope engineering - Simons, N. E. (Thomas Telford, 2001)
This work comprehensively treats soil & rock slope engineering in one volume. It focuses on getting the fundamentals right explaining simple methods of stability analysis, and applying them to a wide range of practical applications.